Evaluation of RFID Propagation Channels with Wooden and Metal Bookshelves Based on Measurement Data - Jatuporn Supramongkonset; Kotchakorn Rattasuwan; Sathaporn Promwong (My University, 2023)
This paper studies the propagation that occurs in Radio Frequency Identification (RFID). The purpose of this study is to establish a model to study the energy and efficiency of the system. Experimenting with two model of bookshelf models. Wood and metal bookshelves are used as models to measure data. Microstrip antenna are used as a transmitter (Tx antenna) and a receiver (Rx antenna) at frequency of 2.45 GHz channels in co-polarization. From the data of this measurement result, we can observe the tendency of path loss arising from the change in distance and the effect of the signal in both wood and metal bookshelf by the contouring of the path loss signal. The results showed that the co-polarization had higher path loss at increased distances. By path loss modeling using contour method it was found that at measuring point near the edge of the bookshelf There is path loss in the edge of metal bookshelf higher than the edges of wooden bookshelf.
Keywords: RFID technology advancements; Indoor and Outdoor Localization Technologies; Antenna Design and Analysis